THE INFLUENCE OF CAPITAL INTENSITY AND INDEPENDENT COMMISSIONERS ON TAX AGGRESSIVENESS - Fitriyah Fitriyah (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Tax avoidance involves strategies aimed at reducing tax obligations, which can have an impact on both national revenues and corporate governance. Companies with high capital intensity tend to employ tax planning techniques that may lead to more aggressive tax positions. The presence of independent commissioners can provide impartial oversight, thereby improving governance and potentially discouraging aggressive tax practices. This research seeks to investigate the influence of Capital Intensity and Independent Commissioners on Tax Aggressiveness within the property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) between 2017-2021. Employing a quantitative approach, the study utilized purposive sampling to select 8 companies with 5 years of financial data, resulting in a total sample size of 40 samples that met specific criteria. Financial statement data was analyzed using various statistical tests, model estimation methods, and regression analyses. The findings suggest that both Capital Intensity and Independent Commissioners collectively impact Tax Aggressiveness, although individually they do not have a significant effect.